Précis. (1st July 2017) - Elshahed, Mohamed; Andersen, Angela
'WRITING HISTORIES OF NOW: MODERN AND CONTEMPORARY MIDDLE EAST ART AND ARCHITECTURE', FORUM TRANSREGIONALE STUDIEN AND DEPARTMENT OF ART AND VISUAL HISTORY (IKB), HUMBOLDT UNIVERSITY, BERLIN, GERMANY, JULY 6–7, 2015'BEYOND THE MOSQUE: DIVERSE SITES OF MUSLIM PRAYER', UNIVERSITIES ART ASSOCIATION OF CANADA/L'ASSOCIATION D'ART DES UNIVERSITÉS DU CANADA ANNUAL CONFERENCE, MONTREAL, CANADA, OCTOBER 27–30, 2016